If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 3x + 4 Reorder the terms: 5 + -1x = 4 + 3x Solving 5 + -1x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -1x + -3x = 4 + 3x + -3x Combine like terms: -1x + -3x = -4x 5 + -4x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -4x = 4 + 0 5 + -4x = 4 Add '-5' to each side of the equation. 5 + -5 + -4x = 4 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 4 + -5 -4x = 4 + -5 Combine like terms: 4 + -5 = -1 -4x = -1 Divide each side by '-4'. x = 0.25 Simplifying x = 0.25
| 3(4v+8)=-8v-16 | | 2*x+4=0 | | 35/(c+2)=7 | | 8n+1=0 | | 6=-7x | | -5y^3+5y^2-7y^2+7y=0 | | n^3-n=4n^2-4 | | (9-u)(3u-5)=0 | | 2w+17=43 | | h=-16t^2+77t+77 | | x(x+8)=180 | | 112-6x=12x+18 | | 12-4x=15-3x | | 5x^2+37+42=0 | | 6x+9y=36 | | 5x^2+37=-42 | | 3-1.2y=2.4 | | 8x^(7/2)-24=0 | | 7/2y-1+13 | | m=-0.5(29)+23 | | 5x+3=19+5 | | 2x^2+18=90 | | 4x^2-31x+21=0 | | 9-7x=90-28x | | 159-2x=34x+23 | | 2(3x+4)=4x-2 | | x(2x-1)*(3x+2)=0 | | x^4-24x^3+144x^2=0 | | 8+2x+3-x=2x-1 | | 4x-12x+9=0 | | x^4-24x^3+14x^2=0 | | -39+r=26 |